Mucosal barrier status in Atlantic salmon fed marine or plant-based diets supplemented with probiotics - Nadanasabesan, Nimalan; Sørensen, Solveig Lysfjord; Fečkaninová, Adriána; Koščová, Jana; Mudroňová, Dagmar; Gancarčíková, Soňa; Vatsos, Ioannis; Saraswathy, Bisa; Kiron, Viswanath; Sørensen, Mette (Aquaculture, 2021)
publishedVersion